An analysis of the relation between reforms implemented by Amir Kabir and Sepahsalar in the judiciary system of the Nasery era - mahmood mortezaeefatd; ali bigdeli; alireza ali soofi (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2018)
During the Naseri era, both Amir Kabir and Sepahsalar had reforming plans for the judiciary system. The most significant challenges of their administration period included the religious versus conventional courts, the extent to which clergymen could intervene in judiciary affairs and a change of attitude in the scope of judiciary affairs. This study has investigated the relationship between these two reformative plans. The results indicates the major reforms implemented by Amor Kabir as follows: the reformation of the religious court, establishing the court of justice (house of justice), revoking the convention of sanctuary and a pay cut for the clergymen, whereas Sepahsalar executed the following reforms: publishing the guide booklet of the judiciary power's court house, enacting laws to support the proletariat rights, restricting the ruler's authority and creating a new judiciary structure. Both reformers tried to strengthen the conventional court against the religious court. It seems that, regardless of similarities, they were following different approaches. Amir must have intended to perform justice through some reforms influenced by Occidental trends, whereas Sepahsalar tried to use the law as a driving force for other sectors of the society to move toward development.